Culture-Based Character Education Communications in Bukit Wolio Indah - Safiuddin (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
The development of culture-based character-based education needs to be a regional program, especially for the people of Bukit Wolio Indah Village. In developing culture-based character communication, it has not been fully maximized so that the development of culture-based character education in Bukit Wolio Indah Village in the spiritual, emotional and intellectual fields has not been so balanced and harmonious. In addition, there are many teenagers and young people who apparently do not know or are not familiar with the existing culture-based character education and it turns out that it contains noble character values. The method of this service activity is a descriptive qualitative study method. This method is the result of the author's ideas which are then developed based on theories that are in accordance with the discussion. The results of this service explain that the process of character building based on culture has been able to instill values that are grown and developed in the form of basic cultural values. These values include honesty, trustworthiness, togetherness, tolerance, responsibility, and caring for others.